Implementation of Local Wisdom Based on Tolerance Character in Pancasila Village, Balun, Lamongan - Susandi, Ari; Inggar Dinanti, Regita; Mandala Putra, Andi (International Journal of Social Science, Education, Communication and Economics, 2025)
Balun Village is one of the Pancasila villages in Lamongan Regency. There are three religions practiced by the village community, namely Islam, Protestant Christianity and Hinduism, they apply moderation and tolerance that varies between religious communities as part of the implementation of Pancasila values. Balun Village is located in Turi sub-district, Lamongan district. This village is often visited by Pancasila tourists from various circles, ranging from elementary school, middle school, high school students, even students who conduct research there. It is good in the village. The nickname of the village "Pancasila" for Balun, Turi sub-district, Lamongan regency, East Java, contains the values of Pancasila and tolerance that develop in it. The village, which is 4 kilometers from the city of Lamongan, is inhabited by three religious adherents who not only respect and appreciate each other but also make inter-religious harmony in their society as an identity for their village. The method used in this study is descriptive qualitative. This approach was chosen because in this study the variable is about "Inter-Religious Tolerance" so that in-depth information is needed through the process of observation, interviews, and documentation.